SISTEM DISPLAY PADA INTERIOR MUSEUM MANUSIA PURBA KLASTER NGEBUNG DI SANGIRAN - Zulfa Miflatul Khoirunnisa; Joko Budiwiyanto (Institut Seni Indonesia Surakarta, 2019)
ABSTRACT Sangiran Sangiran Site is the most complete ancient human site in the world. The museum has several clusters, one of them is Ngebung Cluster which tells the grandeur and greatness of Sangiran. The purpose of this study is to know the interior design and display system of Ngebung Cluster Museum showroom. This study employs qualitative research methods which lead to detailed descriptions and interactive analysis techniques. The results of the research indicate that the interior of the showroom was created to adjust to the existing museum building and was designed in accordance with museum design standards. The composition of interior elements such as wall finishing, flooring and ceiling materials are repeated and plain in order that museum visitors can focus on the displays and collections of the museum. Therefore, the arrangement of furniture and display systems is adjusted to the available space. The display system in the museum's showroom can be said to have met the requirements of a good display, which refers to the principles of the exhibition system and technical requirements that need to be considered in the arrangement of the museum's collection. The presentation, display furniture, and the completeness of information are expected to encourage visitors to understand and interpret what is seen. Meanwhile, based on the results of the research it can be concluded that the display system in the showroom of the Ngebung Archaeological Museum has fulfilled good display standards referring to the principles of exhibition administration and taking into account the technical requirements in organizing museum collections. Keywords: Museum, Sangiran, Display System, Interior Design. ABSTRAK Situs Sangiran merupakan situs manusia purba terlengkap di dunia. Museum tersebut memiliki beberapa klaster, salah satunya yaitu Klaster Ngebung yang menceritakan kemegahan dan kebesaran Sangiran. Tujuan penelitian ini adalah untuk mengetahui desain interior dan sistem display ruang pamer Museum Klaster Ngebung. Penelitian ini menggunakan metode penelitian kualitatif yaitu penelitian yang mengarah pada pendeskripsian secara rinci dan teknik analisis interaktif. Hasil penelitian menyimpulkan bahwa interior ruang pamer diciptakan menyesuaikan dengan bangunan museum yang sudah ada dan didesain sesuai dengan standar perancangan museum. Komposisi elemen interior seperti finishing dinding, bahan lantai dan ceiling yang berulang dan dibuat polos dimaksudkan agar pengunjung museum dapat terfokus pada display dan koleksi yang disajikan museum. Oleh karena itu, penataan perabot serta sistem display disesuaikan dengan ruang yang tersedia. Sistem display di ruang pamer museum ini dapat dikatakan sudah memenuhi syarat display yang baik, yakni mengacu pada prinsip-prinsip tata pameran dan persyaratan teknis yang perlu diperhatikan dalam penataan koleksi museum. Melalui metode penyajian, perabot display, serta didukung dengan kelengkapan informasi pengunjung diharapkan dapat memahami dan menginterpretasi apa yang dilihat. Sementara itu, berdasarkan hasil penelitian dapat disimpulkan bahwa sistem display dalam ruang pamer Museum Manusia Purba Klaster Ngebung sudah memenuhi standar display yang baik mengacu pada prinsip-prinsip tata pameran serta memperhatikan persyaratan teknis dalam melakukan penataan koleksi museum.Kata Kunci: Museum, Sangiran, Sistem Display, Desain Interior.